2016
DOI: 10.1111/jasp.12410
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing actions from a third‐person perspective: effects on health behavior and the moderating role of behavior difficulty

Abstract: Visualizing behavior from a third-person (vs. first-person) perspective can produce stronger motivation to enact the behavior. However, the effects of perspective on health behaviors have been mixed. Hypothesizing that the difficulty of the visualized behavior might moderate the effect of perspective, two experiments manipulated the difficulty of the visualized behaviors (fruit/vegetable consumption; exercise) plus perspective and subsequently measured motivation (Experiments 1 and 2) and behavior (Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…Existing research on the effects of perspective on health behaviour has found large effects (d = 0.75) of perspective on behaviour (Rennie et al, 2016), and so we expected effects of at least medium magnitude. For detecting medium effects using regression analyses with three predictors and significance tests at Alpha = .05, Cohen (1992) suggests a sample size of 76.…”
Section: Methods Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Existing research on the effects of perspective on health behaviour has found large effects (d = 0.75) of perspective on behaviour (Rennie et al, 2016), and so we expected effects of at least medium magnitude. For detecting medium effects using regression analyses with three predictors and significance tests at Alpha = .05, Cohen (1992) suggests a sample size of 76.…”
Section: Methods Participantsmentioning
confidence: 99%
“…In contrast, with the third-person perspective the individual sees the event from the perspective of an observer, viewing themself in the image as well as their surroundings, thereby allowing them to "see the bigger picture". This effect has been observed for a number of different behaviours, such as studying (Vasquez & Buehler, 2007) and voting (Libby, Shaeffer, Eibach, & Slemmer, 2007) as well as health behaviours such as fruit and vegetable consumption and physical activity (Rennie, Harris & Webb, 2016).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations